TIONGHOA INDONESIA:DARI DIKOTOMI KE MONO-IDENTITAS? - Ibrahim, S.Fil., M.Si, - (SOSIOLOGI, 2013)
The most commonly used by various elements in defining Tionghoa identity is by dividing it  into  main  dichotomy,  i.e.  totok  and  peranakan.  Nevertheless,  totok  and  peranakan definition  themselves  have  limits  that  keep  continuously  debated.  Totok  is  generally understood  from  the  side  of  its  birth  and  Tionghoa  Puritanism,  while  peranakan  is comprehended  as  identity  that  mixes  each  other  with  locality.  As  the  time  goes  by,  totok and peranakan dichotomy are not relevant anymore. Recent politic development has led to Tionghoa identity option measured singly by the level of more liquid flexibility.Keyword : Tionghoa, Identity, Totok, and Peranakan